Using photovoice methods as a community-based participatory research tool to advance uptake of clean cooking and improve health: The LPG adoption in Cameroon evaluation studies - Ronzi, Sara; Puzzolo, Elisa; Hyseni, Lirije; Higgerson, James; Stanistreet, Debbi; Hugo, MBatchou Ngahane Bertrand; Bruce, Nigel; Pope, Daniel (Social science & medicine (1982), 2019)
Each year up to 2.6 million people die prematurely from household air pollution (HAP) due to cooking with polluting fuels such as wood and charcoal, particularly in low and middle-income countries (LMICs). The World Health Organisation recommends scaling the adoption of clean fuels to improve maternal and child health. Liquefied Petroleum Gas (LPG) represents a scalable clean fuel that provides health and environmental benefits when used for household energy in LMICs. In Cameroon, over 70% of people rely on biomass for cooking, and the Government aims to increase LPG use from <20% to 58% by 2030. Supporting households make this transition requires involvement of multiple stakeholders and an understanding of perspectives from the community's perspective. We used visual participatory methods ‘Photovoice’ to explore households' perceptions of factors influencing the uptake of LPG for cooking in South-West Cameroon. Two groups of participants from rural (n = 7) and peri-urban (n = 8) areas photographed subjects they identified as preventing and facilitating LPG uptake in their communities. Subsequently, individual interviews (n = 15) and group discussions (n = 5) explored participants' reflections on the photographs. Thematic analysis was conducted using NVivo 10 software. The main barriers identified included difficulty in affording the initial LPG equipment and ongoing refills, scarcity of LPG retail shops and refills, and safety concerns. Facilitators included (i) increasing awareness of the benefits of LPG (e.g. health), (ii) increasing retail outlet density in rural areas, (iii) addressing safety concerns (e.g. replacing damaged cylinders), and (iv) reducing the price of LPG refills. Participants presented their photos at a public exhibition, which generated discussions with key stakeholders (e.g. government ministries) about how best to assist communities in this transition. Photovoice was found to be an innovative and effective approach for exploring how to advance equitable access to LPG from a community perspective and successfully engage with key stakeholders. •Explore factors influencing Liquefied Petroleum Gas (LPG) uptake via photovoice.•Provide new insights into how to advance LPG access from a community perspective.•The high cost of initial LPG equipment acts as a barrier to adoption.•Low retail density makes it difficult to access refills and use LPG regularly.•Increasing awareness around the economic and health benefits of using LPG is key.